The Deformation Dependent Mass Davidson Model - Bonatsos, D.; Georgoudis, P. E.; Lenis, D.; Minkov, N.; Quesne, C. (HNPS Advances in Nuclear Physics, 2020)
The Deformation Dependent Mass Davidson Model is an extension of the well known Bohr-Mottelson Hamiltonian for the atomic nuclei. It primarily refers to the mass dependence on the deformation and secondary to the Davidson behavior for the potential of the Ø-vibration. This article will be devoted solely in the solution of the radial equation. Fitting results for the 162Dy and 238U ground state, β1 and γ1 bands are also presented.